Graduate students’ competence and readiness for research - Marie Ann S. Gonzales; Merilyn P. Juacalla; Benny B. Juacalla (Institute of Advanced Engineering and Science, 2026)
Research competence forms the foundation of graduate students’ academic success and their ability to contribute meaningfully to scholarly output. This study examines the relationship between research competence and research readiness among 224 graduate students from MA in education, EdD, and PhD in Laguna State Polytechnic University selected through a non- random sampling technique, specifically purposive sampling. These participants, who had all completed a research subject, responded to a validated, researcher-developed 5-point Likert scale questionnaire. The study employed quantitative methods, including mean comparison, Spearman rank correlation, and Mann-Whitney U tests, to analyze the data. Findings revealed a strong positive correlation between students’ research competence and their readiness to engage in the research process. Notably, doctoral students demonstrated higher levels of both competence and readiness compared to master’s students. While competence levels were relatively consistent across programs, readiness significantly differed. These results highlight the need for program-level interventions that provide targeted research training and support, contributing to more effective curriculum design and evidence-based policy-making in graduate education.